Content Translation And Validation Of The Pediatric PIV Infiltration Scale Into Brazilian Portuguese - Rodrigues,Elisa da Conceição (2020)
ABSTRACT Objectives: to translate, adapt and validate the PIV Infiltration Scale content into Brazilian Portuguese. Methods: a methodological study. Initial translation was performed by two bilingual translators, translation synthesis; backtranslation to the original language; elaboration of the translated version and adapted by expert consensus; content validation and pretest. Results: the Pediatric PIV Infiltration Scale has been translated and adapted. Discrepancies were sorted out by consensus. The scale content was validated by nine experts, reaching a global content validity index of 0.95. Pretest was performed by applying the scale to 33 intravenous device insertion sites of 17 newborns and 16 children. The predominant infiltration grades were 2 and 3. Conclusions: the Pediatric PIV Infiltration Scale’s translated version achieved equivalence to Brazilian Portuguese and was validated by experts.